4(5g+6h)
You xan remove four from each number, but no letters since they dont have any of the same.
Answer:
<em>B. a = y - k/(x-h)² </em>
Step-by-step explanation:
Given the expression y = a (x-h)² + k
First make a the subject of the formula
Subtract k from both sides
y = a (x-h)² + k
y- k = a (x-h)² + k - k
y - k = a (x-h)²
Divide through by (x-h)²
y - k/(x-h)² = a
a = y - k/(x-h)²
Hence option B is correct
Answer:
y- intercept = - 6
Step-by-step explanation:
The y- intercept is where the graph crosses the y- axis.
Let x = 0 and substitute in to the equation, that is
y = 0² - 3(0) - 6 = 0 - 0 - 6 = - 6 ← y- intercept
First, using the order of operations(PEMDAS), you would solve what is inside the parenthesis.
<span>(8.218 + 9.93) + (17.782 + 0.07)
(</span>18.148) + (17.852)
18.148 + 17.852
Now, all you would have to do is add the two sums.
18.148 + 17.852 = <span>36
</span>
The answer would be 36.
I hope this helps!
Answer:
C
Step-by-step explanation:
Domain of the function is the whole R